Essential Skills Challenges for the 21st Century Graduates: Creating A Generation of High-Level Competence in The Industrial Revolution 4.0 Era - M. Bambang Purwanto; Rudi Hartono; Sri Wahyuni (Asian Journal of Applied Education (AJAE), 2023)
This research discusses the challenges and opportunities for Islamic basic education in the post-Industrial Revolution 4.0 era. Strengthening new literacy for Islamic basic education teachers is a key to change, revitalizing literacy-based curricula, and strengthening the role of teachers who have digital competence. The teacher's role is to build a generation with competence, character, new literacy skills, and higher-order thinking skills. Islamic basic education, as a basis for determining intellectual, spiritual, and emotional intelligence in children, must strengthen 21st-century literacy skills. Starting from the creative aspects, critical thinking, communication, and collaboration. Islamic basic education urgently strengthens new literacy and digital-based curriculum revitalization. Curriculum revitalization refers to the five basic values ​​of good students, namely resilience, adaptability, integrity, competence, and continuous improvement. Islamic basic education educators must be digital teachers, computer savvy, and free from academic ills. The goal is to create a generation of high-level competence, character, and literacy to answer the challenges of the Industrial Revolution 4.0 era.